Self-Support and Loneliness Among Chinese Primary School Students: A Moderated Mediation Model - Yao, Zhendong; Pang, Lu; Yu, Huiying; Xiao, Hanshi; Peng, Biao (Frontiers in Psychology, 2022)
This study examined the effect of self-support on loneliness, the mediation effect of school belonging, and the moderation effect of self-esteem using a sample comprising 1,126 Chinese mainland primary school students. The results showed that (1) self-support had a significantly negative predictive effect on loneliness; (2) the relation between self-support and loneliness was mediated by school belonging; and (3) the relation between school belonging and loneliness was moderated by self-esteem, supporting the moderated mediation model. These results revealed the formation mechanism of loneliness among primary school students and have significant implications for interventions against loneliness in the primary school context.